2009
DOI: 10.1097/iae.0b013e3181934908
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes and Wound Dynamics of Sclerotomy Ports of 20, 25, and 23 Gauge Vitrectomy

Abstract: The small gauge systems are safe and equally effective than the 20-G system for non-complicated vitreous hemorrhage cases with faster recovery and more comfort for the patient. Increased vitreous clogging with small gauge systems does not extrapolate to an increased risk of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 15 publications
7
60
2
2
Order By: Relevance
“…Whereas classical 20G vitrectomy allows vitreous ‘shaving’ at the inner sclerotomy, the removal of the vitreous at the inner sclerotomy site between the 2 mm of the sclerotomy and the end of the cannula with the 23G sutureless system is incomplete. This is supported by an endoscopic analysis of the dynamics of 23G sclerotomy port closure revealing a herniation of vitreous strands into the scleral tunnel [1]. …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Whereas classical 20G vitrectomy allows vitreous ‘shaving’ at the inner sclerotomy, the removal of the vitreous at the inner sclerotomy site between the 2 mm of the sclerotomy and the end of the cannula with the 23G sutureless system is incomplete. This is supported by an endoscopic analysis of the dynamics of 23G sclerotomy port closure revealing a herniation of vitreous strands into the scleral tunnel [1]. …”
Section: Discussionmentioning
confidence: 94%
“…Transconjunctival sutureless vitrectomy provides several advantages over traditional 20-gauge (20G) vitrectomy, including faster wound healing, less conjunctival scarring, improved patient comfort, decreased inflammation, reduced surgically induced astigmatism and a shortening of surgical opening and closing times [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Comparison between 20G and 25G vitrectomy revealed that the time saved was localized to the 'initial' and 'final' steps of the procedure (13). Damage to the conjunctiva was also minimalized with a transconjunctival, sutureless approach (14). This may be of clinical significance in patients requiring glaucoma filtration surgery in the future.…”
Section: Introductionmentioning
confidence: 91%
“…Though post-operative RD subsequent to microincision sutureless PPV has been reported in several studies, 83 the investigators concluded that development of RD did not directly result from the microincision 23G or 25G technique. 69 In a study, Ibarra et al reported a RD incidence of 2.2 % after macular hole repair.…”
Section: Retinal Detachmentmentioning
confidence: 99%